Young Mothers' Experiences of Receiving the Baby Bonus: A Qualitative Study. Issue 1 (2nd January 2017) - Garrett, Cameryn C.; Keogh, Louise; Hewitt, Belinda; Newton, Danielle C.; Kavanagh, Anne M.
ABSTRACT: The year 2014 marked the abolition of the Baby Bonus and its replacement with a substantially reduced parenting payment. While often criticised as "middle-class welfare, " or publicly denounced due to its purported misuse by disadvantaged mothers, this paper argues that the Baby Bonus provided valuable financial assistance to families experiencing high financial stress. To investigate young women's experience of receiving the Baby Bonus, 19 semistructured interviews were conducted with young mothers in Melbourne who had recently had babies. Many were experiencing financial stress and this payment provided much needed financial support for the basic costs arising from having a baby. Several mothers perceived work as a luxury that was out of reach due to high childcare costs relative to their earning capacity and therefore saw Paid Parental Leave as a further privilege unavailable to them. Our results suggest that while the concerns of policymakers to achieve the best use of scarce resources are critical, it should also be acknowledged that the policy change may have serious implications for many young mothers and may exacerbate disadvantage, and young mothers' sense of alienation, ultimately leading to greater inequalities.